Book review: Child Poverty: Aspiring to Survive by Morag C Treanor - Kate Mackinnon; Rosie Moore (Scottish Journal of Residential Child Care)
Aspiring to Survive was published in February of 2020, at the precipice of the Covid-19 pandemic which has impacted every aspect of our lives and shone a harsh light on the inequalities in our society, as well as exacerbating them. In Aspiring to Survive, Treanor asserts that child poverty is never inevitable, and that even in times of financial scarcity the right government decisions can prevent it.